An Overview of Parkinson's Disease and the Cannabinoid System and Possible Benefits of Cannabinoid-Based Treatments - Lastres-Becker, Isabel; Fernandez-Ruiz, Javier (Current Medicinal Chemistry, 2006)
Parkinson's disease (PD) is a slowly progressive neurodegenerative disorder with a heterogeneous clinical picture and a variable rate of progression. PD is characterized by degeneration of the pigmented neuromelanin bearing cells of the pars compacta of the substantia nigra that leads to a severe dopaminergic denervation of the striatum. Current treatments for PD rely on dopamine replacement therapy, most commonly with the dopamine precursor levodopa. Despite the many recent advances in the symptomatic treatment of PD, there is still no realistic prospect for a cure. In recent years, new data support the idea of a relevant role for the cannabinoid system in PD. As cannabinoids have neuroprotective properties, they have been proposed as potentially useful neuroprotective substances in PD, as well as to alleviate some symptoms in specific circumstances (i.e. parkinsonian tremor associated with overactivity to the subthalamic nucleus; levodopainduced dyskinesia). By contrast, CB1 receptor antagonists might be useful to reduce bradykinesia in patients refractory to classic levodopa treatment. The present article will review all data about the relationship between PD and the cannabinoid system including: i) the usefulness of cannabinoid-related compounds to alleviate some PD symptoms; ii) that cannabinoid-based compounds might provide protection against the progression of neuronal injury characteristic of this disease; iii) the influence of cannabinoids on local inflammatory events associated with the pathogenesis in PD. Collectively, all these evidence support that the management of the cannabinoid system might represent a new approach to the treatment of PD.
Keywords: Cannabinoids